Association between immigration enforcement encounters and COVID-19 testing and delays in care: a cross-sectional study of undocumented young adult immigrants in california - May Sudhinaraset; Hye Young Choi; Ezinne Nwankwo; Maria-Elena De Trinidad Young (BMC, 2022)
Abstract Background Undocumented immigrants are expected to face increased risks related to COVID-19 due to marginalizing restrictive immigration policies. However, few studies have assessed the prevalence of direct encounters with the immigration enforcement system among the undocumented and its impacts on their COVID-related health behaviors and outcomes. In this study, we quantify undocumented immigrants' lifetime exposure to various immigration enforcement tactics and their association with delays in COVID-19 testing and healthcare behaviors. Methods This cross-sectional study included a non-random sample of 326 Asian and Latinx undocumented immigrants in California from September 2020 to February 2021. The primary exposure was immigration enforcement encounter scores ranging from 0-9, assessed through self-reports of direct experiences with the immigration system, immigration officials, and law enforcement. The main outcomes were positive test for COVID-19, had or suspected having COVID-19, and delayed or avoided testing and/or treatment for COVID-19 due to immigration status. We used multivariable logistic regression models to examine the association between the primary exposure and outcomes of interest. Results Among 326 participants, 7% had received a positive COVID-19 test result, while 43% reported having or suspected having COVID-19. Almost 13% delayed or avoided COVID-19 testing and/or treatment because of their immigration status. Overall, an increase in immigration enforcement encounters was associated with higher odds of suspecting having had COVID-19 (aOR = 1.13; 95% CI: 1.01,1.26). Reporting an additional enforcement encounter was associated with higher odds of delaying or avoiding testing and/or treatment because of immigration status (aOR = 1.53, 95% CI: 1.26,1.86). Compared to their Latino counterparts, Asian respondents were more likely to report higher odds of delaying or avoiding testing and/or treatment (aOR = 3.13, 95% CI: 1.17,8.42). There were no significant associations between the enforcement score and testing positive for COVID-19. Additionally, while Latinxs were more likely to report immigration enforcement encounters than Asians, there were no differences in the effects of race on COVID-19 testing and healthcare behaviors in models with race as an interaction term (p < 0.05). Conclusions Immigration enforcement encounters compound barriers to COVID-19 testing and treatment for undocumented immigrants.